Survival, Movement, and Habitat Use of Translocated Northern Bobwhite in Texas - Ricardo Cagigal Perez; Nova J Silvy; Brian L. Pierce; Therese A. Catanach (National Quail Symposium Proceedings, 2022)
For decades there has been a noticeable decline in northern bobwhite (Colinus virginianus; hereafter, bobwhite) populations. Few studies have assessed the survival of translocated bobwhite. We evaluated the effectiveness of reintroduction of bobwhite into the Texas (USA) Parks and Wildlife Department’s Gus Engeling Wildlife Management Area (GEWMA), where they had been extirpated but now have suitable habitat. Before reintroduction, GEWMA was surveyed (spring call counts) to make sure no bobwhite were present. Forty-six bobwhite were trapped from March–April 2019 in South Texas, banded, bled, radio-tagged, transported to GEWMA, and released. In addition, 17 bobwhite were trapped banded, bled, radio-tagged, and released back into the source population as a control for comparison of movements, reproduction, and survival estimate differences between the source and released bobwhite populations. During July 2019, 3 broods (24 bobwhite) were trapped and translocated from a South Texas ranch to the GEWMA. Survival for bobwhite released at GEWMA was 37.0% through 1 July 2019 and 70.6% for bobwhite left on the ranch in South Texas. Three nests were found at GEWMA while none were found on the ranch in South Texas. Movement distances between daily locations for males and females did not differ at GEWMA or at the ranch in South Texas; however, there was a significant (P ≤ 0.001) difference in daily movement for bobwhite at GEWMA and the South Texas ranch. Female bobwhite at GEWMA moved 5.4 times the distance of female bobwhite in South Texas and male bobwhite at GEWMA moved 5.9 times the distance of male bobwhite in South Texas. Bobwhite at GEWMA were located in woody cover only 24.2% of the time, whereas bobwhite in South Texas were located in woody cover 76.1% of the time. The greater daily movement and less use of woody cover for bobwhite at GEWMA probably contributed to their lower survival.
Keywords: Colinus virginianus; habitat use; movements; northern bobwhite; reproduction; survival; Texas; translocation.